2018
DOI: 10.1016/j.jad.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension risk and clinical care in patients with bipolar disorder or schizophrenia; a systematic review and meta-analysis

Abstract: Limited evidence suggests that patients with BPD have a higher risk of HTN. Patients with schizophrenia and BPD receive poor care of HTN. Understanding the risk of HTN, and the differences in its care, is essential for clinicians to reduce the cardiovascular morbidity and overall mortality of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 48 publications
1
36
0
3
Order By: Relevance
“…39 Patients with bipolar disorders are also at higher risk for inflammation-associated metabolic syndromes such as myocardial infarction, stroke, atherosclerosis and hypertension. 11,[40][41][42][43] Examination of post-mortem brain tissue can provide valuable insights into a possible association between mood disorders and neuroinflammation. In a meta-analysis of post-mortem studies of brains of patients with MDD measuring cytokines, chemokines and cell-specific markers of microglia and astrocytes, two studies found increased markers of microglia in MDD and four studies found no differences between MDD and healthy controls.…”
Section: Resultsmentioning
confidence: 99%
“…39 Patients with bipolar disorders are also at higher risk for inflammation-associated metabolic syndromes such as myocardial infarction, stroke, atherosclerosis and hypertension. 11,[40][41][42][43] Examination of post-mortem brain tissue can provide valuable insights into a possible association between mood disorders and neuroinflammation. In a meta-analysis of post-mortem studies of brains of patients with MDD measuring cytokines, chemokines and cell-specific markers of microglia and astrocytes, two studies found increased markers of microglia in MDD and four studies found no differences between MDD and healthy controls.…”
Section: Resultsmentioning
confidence: 99%
“…Primary hypertension is a systemic and complicated disease often accompanied by glycometabolism and lipid metabolism disorders, as well as organic or functional changes in the heart, kidney, brain, and retina, which seriously impairs patient health [5]. The pathogenesis of primary hypertension is complicated.…”
Section: Discussionmentioning
confidence: 99%
“…A recent large representative cohort study in Taiwan showed that schizophrenia patients were 1.93 times more likely to be diagnosed with hypertension in the year before schizophrenia was diagnosed ( 76 ). A possible explanation for the disparity in results is that blood pressure in BD, schizophrenia and MDD patients is poorly recorded and that this may have led previous studies to underestimate the risk of hypertension in SMI patients ( 75 , 77 ).…”
Section: Hypertensionmentioning
confidence: 95%
“…A meta-analysis found that, compared with matched general population controls, people with SMI do not seem to have a significantly increased risk for hypertension (p = 0.07) ( 16 , 52 ). However, another recent meta-analysis in BD and schizophrenia patients did report an increased risk for hypertension in BD patients (Incidence Rate Ratio = 1.27) ( 75 ). A recent large representative cohort study in Taiwan showed that schizophrenia patients were 1.93 times more likely to be diagnosed with hypertension in the year before schizophrenia was diagnosed ( 76 ).…”
Section: Hypertensionmentioning
confidence: 99%